2009
DOI: 10.1103/physrevb.80.064402
|View full text |Cite
|
Sign up to set email alerts
|

Lattice-form-dependent orbital shape and charge disproportionation in charge- and orbital-ordered manganites

Abstract: The orbital shapes and charge disproportionations at nominal Mn 3+ and Mn 4+ sites for the chargeand orbital-ordered phases have been studied on half-doped manganites Pr(Sr0.1Ca0.9)2Mn2O7 and Eu0.5Ca1.5MnO4 with double-layer and single-layer Mn-O networks, respectively, by means of xray structural analyses, in comparison with Pr0.5Ca0.5MnO3 with the pseudo cubic network. In a single-layer Eu0.5Ca1.5MnO4 system, the (y 2 −z 2 )/(z 2 −x 2 )-type orbital shape is observed, while the (3y 2 −r 2 )/(3x 2 −r 2 )-type… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 46 publications
8
22
0
Order By: Relevance
“…The simulated HAADF-STEM image based on this model (as insetted in the right of Fig. 5(b)) shows a good agreement with the experimental results, in contrast to the disordered phase of Pr(Ca 0.9 Sr 0.1 ) 2 Mn 2 O 7 , 40 where both Ca and Pr atoms locate at the cages of the MnO 6 octahedra and also in the AO layers.…”
Section: Fig 3 (A)supporting
confidence: 71%
See 1 more Smart Citation
“…The simulated HAADF-STEM image based on this model (as insetted in the right of Fig. 5(b)) shows a good agreement with the experimental results, in contrast to the disordered phase of Pr(Ca 0.9 Sr 0.1 ) 2 Mn 2 O 7 , 40 where both Ca and Pr atoms locate at the cages of the MnO 6 octahedra and also in the AO layers.…”
Section: Fig 3 (A)supporting
confidence: 71%
“…5(b) is characterized by whiter spots arranged in line (emphasized by arrows in the right) and located in the middle of the two adjacent dark lines (rock salt layers), implying that the heavy Pr atoms (the whiter spots) locate inbetween the bilayer MnO 6 layers, which is not concordant with the results by X-ray diffraction. 13,40 A structural model of PrCa 2 Mn 2 O 7 with Pr atoms only located in-between the bilayer MnO 6 layers is therefore proposed in Fig. 5(c).…”
Section: Fig 3 (A)mentioning
confidence: 99%
“…48 This description shares the theoretical results of Ferrari et al, 53 who proposed that the CO-OO ordering in La 0.5 Ca 0.5 MnO 3 is better described by a charge-density wave of oxygen holes. Not far from this vision, Okuyama et al 54 more recently reported on a possible correlation between the dimensionality of the lattice and the charge segregation in manganites, which they found to be far from ionic in all studied cases by an x-ray structural study. They conclude that single-layered (n = 1) systems should generally show a negligible charge disproportionation between Mn sites, notably smaller than for the nonlayered case (n = ∞).…”
Section: Discussionmentioning
confidence: 98%
“…The ordered orbitals have been suggested to be d 3x 2 −z 2 and d 3y 2 −z 2 12,27,28 . Meanwhile, some x-ray scattering experiments 29,30 combined with local-density approximation including on-site Coulomb interactions (LDA+U) calculations 30 indicate that the orbital ordering is dominated by d x 2 −z 2 and d y 2 −z 2 , which is also supported by means of x-ray structural analyses 31 . To further examine this issue, we have performed the mean field calculations to examine the ordering between a general linear combination of d 3z 2 −r 2 and d x 2 −y 2 , and have found that the ordering between + and − has the lowest energy, which is also consistent with our RPA analysis.…”
Section: Phase Diagram and Phase Transitionmentioning
confidence: 74%